The challenges and opportunities of visually impaired students in inclusive education: The case of Bedlu - Mulat Alebachew Belay; Sileshi Goshu Yihun (Journal of Pedagogical Research, 2020)
Despite many efforts invested in for the successful implementation of inclusive Education in public primary and secondary schools in Ethiopia, there are still numerous challenges facing this area. This paper describes the challenges and opportunities in an inclusive education of a visually impaired student, Bedlu. In undertaking the study, a case study design was employed. In order to examine the thoughts of Bedlu, he was interviewed about his experiences at his school and in his class. In addition, his school and classroom setting was observed. Content analysis was done on the transcriptions of the interview data and the field notes. The findings show that even though there are some opportunities that support inclusive education, these opportunities do not guarantee their implementation effectively. The interview results indicated that inadequate budget, lack of necessary materials, absence of qualified professionals, shortage of professional growth, and development trainings were some of the major factors that hinder the full implementation of inclusive education. It was also concluded that the challenges outweigh the opportunity on the full implementation of inclusive education. As a recommendation, strong collaboration among stakeholders, non-governmental organizations along with the concerned bodies, training offered for professional teachers in special needs education, and appropriate budget allocation in order to realize the effective implementation of inclusive education were suggested.